Analysis Of Marketing Strategy Of Eiger Adventure Brand From Indonesia Worldwide - Sindi Apridayanti; Warganegara, Tri Lestira Putri (SEAN Institute, 2024)
This research aims to determine the marketing strategy implemented by Eiger Adventure in introducing local Indonesian brands to the world. The informants in this research were 3 employees, Eiger and its competitors. The analysis method uses IFAS analysis, EFAS analysis, and SWOT analysis. Based on the description and discussion that has been presented, several main points can be drawn from the SWOT analysis as well as strategies that can be implemented by Eiger Adventure based on the alternative strength-opportunity (SO) strategy, namely (1) Determining affordable prices for Eiger Products and helping with travel consumers so that consumers will become more loyal. (2) Improving the product quality of Eiger Products that are suitable for all ages in order to attract consumers. (3) Improving quality and quality so that market demand increases and carrying out more innovative advertising that can attract consumer interest in purchasing Eiger Products.